The Application of Neural Radiance Fields (NeRF) in Generating Digital Surface Models from UAV Imagery - Abate, Dante; Themistocleous, Kyriacos; Hadjimitsis, Diofantos G. (My University, 2024)
Neural Radiance Fields (NeRFs) is emerging as an innovative approach for generating in the reality-based 3D modelling techniques by employing an artificial neural network that optimizes a volumetric scene function based on a collection of input views [1], [2], [3]. This approach offers unprecedented prospects for multiscale 3D modelling and analysis.This study delves into the application of NeRF technology for processing aerial-born imagery [4] to evaluate its effectiveness for the creation of Digital Surface Models (DSM) compared with traditional photogrammetric techniques.
Keywords: NeRF; Photogrammetry; Digital Surface Model; UAV